Saint Lucia. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Santa Lucia during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as agribusiness, training, technology, leadership, trade, rural development, waste management, food safety, biodigesters, biogas, nurseries, inclusion of women and youth, water pollution, and pig and meat production.